Activity of blood plasma adenosine deaminase and mononuclear cell lysates in pulmonary tuberculosis patients with different levels of resistance to anti-tuberculosis agents - O. O. Yanovich; L. P. Titov; M. I. Dus'mikeyeva; N. S. Shpakovskaya (Туберкулез и болезни лёгких)
The purpose of this research is to investigate the activity of adenosine deaminase and its isozymes in pulmonary tuberculosis patients depending on resistance of mycobacteria to anti-tuberculosis agents.It has been found out that the ADA level on blood plasma is higher in the patients with drug resistant mycobacteria, in the patients with multiple/extensive drug resistant mycobacteria (M/XDR) insignificant increase on enzyme activity has been observed, which can be the evidence of the immune system activity suppression.It has been shown that in case of drug susceptible pulmonary tuberculosis the increase of general ADA activity in blood plasma is due to increase of activity in both isozymes and in patients with M/XDR mycobacteria the increase of enzyme activity happens due to the increase in ADA2.